2022
DOI: 10.1121/10.0011694
|View full text |Cite
|
Sign up to set email alerts
|

Estimated cochlear neural degeneration is associated with loudness hypersensitivity in individuals with normal audiograms

Abstract: In animal models, cochlear neural degeneration (CND) is associated with excess central gain and hyperacusis, but a compelling link between reduced cochlear neural inputs and heightened loudness perception in humans remains elusive. The present study examined whether greater estimated cochlear neural degeneration (eCND) in human participants with normal hearing thresholds is associated with heightened loudness perception and sound aversion. Results demonstrated that loudness perception was heightened in ears wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The additional loss of auditory nerve afferent synapses onto IHCs ( Figure 1D ) would not be expected to affect hearing thresholds, but could have other influences on sound perception ( Chambers et al, 2016a ; Henry and Abrams, 2021 ; Lobarinas et al, 2013 ; Resnik and Polley, 2021 ). For example, we recently reported that human subjects with normal hearing thresholds but asymmetric degeneration of the left and right auditory nerve perceive tones of fixed physical intensity as louder in the ear with poor auditory nerve integrity, particularly for low intensities near sensation level ( Jahn et al, 2022 ). To determine whether mice may be showing evidence of auditory hypersensitivity, we performed a closer inspection of the mouse psychometric detection functions for the spared 8 kHz tone.…”
Section: Resultsmentioning
confidence: 99%
“…The additional loss of auditory nerve afferent synapses onto IHCs ( Figure 1D ) would not be expected to affect hearing thresholds, but could have other influences on sound perception ( Chambers et al, 2016a ; Henry and Abrams, 2021 ; Lobarinas et al, 2013 ; Resnik and Polley, 2021 ). For example, we recently reported that human subjects with normal hearing thresholds but asymmetric degeneration of the left and right auditory nerve perceive tones of fixed physical intensity as louder in the ear with poor auditory nerve integrity, particularly for low intensities near sensation level ( Jahn et al, 2022 ). To determine whether mice may be showing evidence of auditory hypersensitivity, we performed a closer inspection of the mouse psychometric detection functions for the spared 8 kHz tone.…”
Section: Resultsmentioning
confidence: 99%
“…We entered the following search terms in Pubmed and found only a single human study of the relationship between physiological indicators of deafferentation and hyperacusis: “hyperacusis synaptopathy,” “hyperacusis hidden hearing loss,” “hyperacusis deafferentation,” and “hyperacusis neural degeneration.” In a small sample of 12 adults with clinically normal hearing and an asymmetric summating potential (SP)/action potential (AP) ratio (a proposed indicator of cochlear deafferentation), Jahn et al (2022) evaluated loudness growth perception in both ears. They found that, on average, the ear with greater estimated cochlear deafferentation (larger SP/AP ratio) showed elevated loudness perception when compared with the contralateral ear of the same participant.…”
Section: Perceptual Consequences Of Cochlear Deafferentation In Human...mentioning
confidence: 99%